Religious Moral Values and the Menace of Corruption in Nigeria - Atoi, Ewere Nelson; Sadiku, Andrew Ohifemen; Kume, Yakubu Babale (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
A fundamental social reality about Nigeria is that majority of its citizens are very religious, yet corruption pervades nearly every stratum of the society. One big task before every rational mind is how to reconcile the extreme religiosity of the citizens with the overwhelming corruption in the country. Therefore, this study examined the nexus between religious moral values and corruption in Nigeria with a view to ascertain the reason why corrupt practices pervade the public and private life of many Nigerian religious adherents. Data was generated from existing literature and careful observation of the state of the nation, and subjected to critical and constructive analysis. This study discovered that there is so much religiosity and less morality in Nigeria. The writers observed that the hypocritical and greedy attitudes of some religious adherents and their inability to apply the core moral values inherent in Christianity, Islam and African traditional religion in their daily conducts are the principal factors escalating the problem of corruption in Nigeria. Some religious adherents place very little premium on the all-important issues of good conduct, discipline, loyalty, patriotism, accountability, transparency, social justice, covenant-keeping and other positive values in their daily dealings. The authors therefore, encouraged Nigerians to internalize the core moral values inherent in the countryâ€™s tripartite religious heritage and apply them to their daily conducts in order to curtail the menace of corruption in Nigeria.     Keywords: Religiosity, Religious Moral Values, Religious Adherents, Corruption, Nigeria